Landscape Design as Art: An Experimental Methodology with the Use of Neurographic Art and Metaball Geometry (International Journal of Built Environment and Sustainability, 2025)
With the use of new technological solutions, non-Euclidean forms can be created in various software platforms and can be produced or fabricated in order to be parts of real world design works. Therefore, new methodology proposals for creation of non-Euclidean forms can be helpful to both designers and design students. In this study, an experimental landscape design methodology which is carried out within the scope of Ozyegin University, Department of Architecture, Architectural Design Studio V and Parametric Design courses, is presented and discussed. Neurographic art is used as a manual art case and metaball script is used as a digital art case of this method. This method has been evaluated and discussed from the perspective of the educators and students. As a result, it has been concluded that the proposed landscape design methodology can be used for the creation of non-Euclidean landscape design forms.
Keywords: Neurographic art, Metaball, Parametric design, Landscape design, Design education.